Refleksi Prinsip Keadilan dalam Perjanjian Waralaba di Indonesia - Batu Bara, Radja Marihat; Tanjung, Ali Asdon; Purba, Bonaraja (Universitas Pahlawan Tuanku Tambusai, 2025)
An agreement is essentially the result of a meeting of minds/mutual assent between parties who wish to achieve a common goal. This goal should provide balanced benefits for all parties involved. As a legal instrument, an agreement should ideally reflect three fundamental elements as stated by Gustav Radbruch, namely justice, expediency, and legal certainty. However, in practice, the principle of legal certainty, especially derived from the principle of pacta sunt servanda, is often given a more dominant emphasis, thus sometimes subordinating the element of justice in contractual relations.This phenomenon is very visible in the practice of franchise agreements, especially those originating from foreign entities, where the structure of the agreement often favors the franchisor. The unbalanced bargaining position results in franchisees having no room for negotiation of the clauses that have been standardized by the franchisor. This paper aims to analyze the root causes of this inequality, identify factors that strengthen the dominance of the franchisor, and offer normative solutions to injustice in franchise agreements.This research uses a normative philosophical approach, namely by analyzing the substance of the contract based on the applicable laws and regulations and the principles of agreement law. The results of the study show that the injustice to franchisees is mainly caused by the inequality of bargaining position between the party that controls the franchise system and the party that depends on the system to run the business. This imbalance causes the content of the contract to be fully determined by the franchisor, so that the alignment of their interests is very dominant, while the protection of franchisees is minimal.